Antibiotic profile of viridans streptococci group isolated of oral cavity from patients with prolonged use of antibiotics - González, Andrea (2022)
Viridans group streptococci (VGS) are a heterogeneous group of saprophytic facultative anaerobic bacteria that are part of the normal flora of the oral cavity. The increased resistance to multiple antibiotics in this group of bacteria becomes important in prolonged antibiotic therapies inpatient where these common microorganisms are replaced by multi-resistant bacteria. Objectives: To determine the percentage of VGS strains isolated from oral cavity resistant to antibiotics used in hospital infectious diseases. Material and Methods: This is a descriptive cross-sectional study that included 60 hospitalized patients with a history of antibiotic therapy for more than 3 weeks. The samples were processed following standardized protocols for collection, isolation and identification of oral cavity VGS and a protocol of antibiotic susceptibility testing. The results are shown in tables and graphics of absolute and relative frequencies. Results: The main indication for antibiotic therapy was orofacial infection with a 28.33%. Penicillin was the antibiotic further used either in single, combined or multiple therapies in all patients. A total of 108 samples (1.8 per patient swabs) were collected. The predominantly identified specie was Streptococcus mutans. The 96.3% of all VGS strains were sensitive to all antibiotics included in the panel. Conclusion: Using different combinations and types of antibiotic therapy inpatient has no effect on the susceptibility of VGS isolated from oral cavity separate from treatment.